Genetic structure and forensic characteristics of the Korean population revealed by GoldenEye 20A - Jin-Feng Xuan; Atif Adnan; Absar Ahmad Zafar; Guanglin He; Xiao-na Li (Taylor & Francis Group, 2020)
Background In China, most Koreans live in the Northeast, including Jilin (59.64%), Heilongjiang (20.21%), and Liaoning (12.55%) provinces, while the rest are spread to other parts of China. Koreans across China share a common culture, which is similar to Korea. Aim The Combined DNA Index System or CODIS has been increased from thirteen to twenty loci, so it is important to generate improved profiles with the help of these additional loci. Subjects and methods In the current study we have analysed 564 unrelated individuals from the Yanbian Korean population using the GoldenEyeTM 20 A kit (Beijing PeopleSpot Inc). Allelic frequencies, population comparisons and forensic statistical parameters of commonly used short tandem repeats were calculated for the Yanbian Korean population from Jilin province, P.R. China. Results A total of 232 alleles were observed and all the loci were found to be in Hardy-Weinberg equilibrium after Bonferroni correction. The combined power of discrimination was 99. 999999999999999999999913% and the combined power of exclusion was 0.999999995349261. Conclusion Phylogenetic parameters showed that the Yanbian Koreans living in Jilin had the closest genetic relationship with South Koreans and other East Asian populations. The present study provides a precise reference database of Jilin Koreans for forensic applications and studies of population genetics.